From human genome to cancer genome: The first decade - Wheeler, David A.; Wang, Linghua (Genome Research, 2013)
The realization that cancer progression required the participation of cellular genes provided one of several key rationales, in 1986, for embarking on the human genome project. Only with a reference genome sequence could the full spectrum of somatic changes leading to cancer be understood. Since its completion in 2003, the human reference genome sequence has fulfilled its promise as a foundational tool to illuminate the pathogenesis of cancer. Herein, we review the key historical milestones in cancer genomics since the completion of the genome, and some of the novel discoveries that are shaping our current understanding of cancer.